Planar sensor for noise cancellation during partial discharge detection in open substation - Kayser Azam, S. M.; Othman, Mohamadariff; Illias, Hazlee Azil; Abdul Latef, Tarik; Daniar Fahmi, Wan Nor Liza Wan Mahadi; Ain, Mohd Fadzil; Hossain, A K M Zakir (Institute of Electrical and Electronics Engineers Inc., 2023)
In compliance with next-generation high-voltage substations, ultrahigh-frequency (UHF) planar sensors are becoming more popular than ever for their online features in partial discharge (PD) diagnostics. However, PD signals mixing with different noises still exist as a major challenge for UHF sensors. Especially in open substations, telecommunication interferences become predominant noise sources to an external UHF sensor placed outside of the equipment chamber. Even though band-stop filters are additionally connected to UHF sensors for denoising, the inherent noise cancellation mechanism is not yet found in any UHF sensor. With the best of our knowledge and survey, we are the first to introduce here a planar sensor that inherently eliminates telecommunication interferences during PD detection (PDD) for open substations even without using any postprocessing filters. To design our sensor, we have applied techniques of truncated partial ground plane for wideband characteristics and modified radiating patch for enhanced gain performance. A novel intermingled coupling resonator is designed to remove the GSM-900 band from within the sensor bandwidth. We have tested our prototype both for free-space propagation and PDD performances. The prototype has a compact physical size of 16 × 8 cm2 and an operational bandwidth of 792–1414 MHz. For a surface discharge source, the prototype successfully detects the PD signals at the earliest stage. Our prototype minimizes the ambient noise floor to 2.5 mV and improves the signal-to-noise ratio by more than 27.9 dB, which is relatively higher than conventional UHF sensors. The proposed sensor also has the potential of classifying PD sources.